Services Marketing : People, Technology, Strategy - Lovelock, Christopher ; Wirtz, Jochen and Chatterjee, Jayanta (Noida, India Pearson Educations, 2016)
This text takes a strongly managerial perspective [of services marketing], yet [it] is rooted in solid academic research. [The authors'] goal is to bridge the all-too-frequent gap between theory and the real world ... The text is equally suitable for courses directed at advanced undergraduates or MBA and EMBA students.
Include Index
Keywords: Service industries--Marketing -- Professions--Marketing -- Customer services--Marketing